Assessment of Radiation Dose from Natural Radionuclides Content of Powdered Milk in Malaysia - Mohd Faizra, Adlyn Hanani; Yusmadi, Rabi’atul Adawiyah; A’zizi, Nurul Azizatul Adawiyah; Sharip, Norazreen (Multidisciplinary Applied Research and Innovation, 2025)
Powdered milk is an essential dietary that is consumed by all age ranges which provides necessary nutrient, mostly important for growth and development of infants, children and for elderly. Objective of this assessment are to determine types of radionuclides in powdered milk, to assess the activities of radionuclides and compare the mean annual effective dose of powdered milk that were selected based on age level categories which is infants, children and elderly. Based on the result, element Potassium (K) and Sulfur (S8) have found in sample by using x-ray diffraction (XRD). For element Sulfur (S8), it is found in sample brands Dutch Lady, Enercal, Ensure, Lactogen and S26(CR) which all of these sample show the same reading, volume 1796.72 while density 1.76µg/cm3. From XRD, total activity of radionuclides can be calculated, which the highest value was 30.39958 (Bq) for sample S26. While the lowest value was 24.452176 (Bq). Among the samples that had been analyzed, Dutch Lady showed low level of radioactivity while S26 showed the highest. However, it value still lower than the ICRP public dose limit which is 1mSv per year.